1993
DOI: 10.1128/jb.175.6.1717-1722.1993
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of a choline-containing teichoic acid in the maintenance of normal cell shape and physiology in Streptococcus oralis

Abstract: Streptococcus oralis ATCC 35037 took up radioactively labeled choline from growth medium. Most of the choline (80 to 90%o) was incorporated into the cell wall teichoic acid, and about 10%Y was localized in the plasma membrane. While cells grew in choline-free medium, they did so at slow rates and produced cell walls with greatly reduced amounts of phosphate and no detectable choline. Cells grown in choline-free medium had grossly abnormal shape and size. Both biochemical and morphological abnormalities were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…However, the synthesis of phosphatidylcholine by most prokaryotes for their membranes has not been demonstrated (Moat, 1979), suggesting that this possible use for choline is possible but unlikely. The growth of several Gram-positive organisms in the absence (Horne & Tomasz, 1993) or in an excess (Podvin et al, 1988) of choline was shown to result in severely affected cell shape, cell division and overall physiology. Perhaps a high choline content in the yeast extract of LB affected ANG-SQIT, leading to celldivision defects (data not shown) and eventual cell death.…”
Section: Discussionmentioning
confidence: 99%
“…However, the synthesis of phosphatidylcholine by most prokaryotes for their membranes has not been demonstrated (Moat, 1979), suggesting that this possible use for choline is possible but unlikely. The growth of several Gram-positive organisms in the absence (Horne & Tomasz, 1993) or in an excess (Podvin et al, 1988) of choline was shown to result in severely affected cell shape, cell division and overall physiology. Perhaps a high choline content in the yeast extract of LB affected ANG-SQIT, leading to celldivision defects (data not shown) and eventual cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial Strains, Plasmids, and Growth Media-Cultures of S. pneumoniae R36A, a non-encapsulated laboratory strain from the Rockefeller University collection, were grown in a casein-based semi-synthetic medium (C ϩ Y) containing 1 mg/ml yeast extract (7) or in a chemically defined medium (Cden) (8) at 37°C without aeration. Plasmid pJDC9 (9) was used for insertion duplication mutagenesis.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike the pneumococcus, however, S. oralis has no nutritional requirement for choline and when grown in its absence, PChofree TA seems to be incorporated into the cell wall, although the cells show a grossly abnormal shape and size (16). That is, in contrast to the uniform size of normal cells, choline-free bacteria showed a wide distribution of sizes.…”
mentioning
confidence: 98%